Examining long-acting reversible contraception non-use among Australian women in their 20s: findings from a qualitative study. Issue 7 (3rd July 2019) - Coombe, Jacqueline; Harris, Melissa. L.; Loxton, Deborah
Abstract: Australian women use less effective, short-term methods of contraception more often than any other method, despite the availability of much more effective long-acting reversible contraception (LARC). Although research examining the low uptake of LARC among Australian women has increased over the past few years, we still know little about the factors influencing this phenomenon. Using data from semi-structured telephone interviews with 15 Australian women in their 20s, this paper explores contraceptive experience to better understand the non-use of LARC. Findings highlight the ubiquity of the use of the oral contraceptive pill and perceptions of LARC as a more serious contraceptive choice. Among participants, the intrauterine device (IUD) was viewed particularly unfavourably. Furthermore, LARC was shown to be only considered for use after dissatisfaction with shorter-term methods (usually the Pill) if at all. Overall, these findings suggest further education in dispelling myths and discomfort around LARC use, while simultaneously recognising and respecting women's decisions to not use LARC methods.